THE DETERMINANTS OF INTELLECTUAL CAPITAL DISCLOSURE - HERRI SUGANDI; IRWANTO HANDOJO (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2018)
The objective of this research is to obtain empirical evidence about the influence of company size, corporate governance, leverage, profitability, industry, listing age, type of auditor, and intellectual capital level as independent variables on intellectual capital disclosure as dependent variable in non-financial companies listed in Indonesian Stock Exchange. The population in this research is all listed non-financial companies in Indonesia Stock Exchange during 2013 to 2015. Sample is obtained through purposive sampling method, in which 185 listed nonfinancial companies in Indonesia Stock Exchange meet the sampling criteria resulting 555 data available are taken as sample. Multiple linear regression is used as the data analysis method in this research. The result of this research shows that three variables – company size, type of auditor, and industry statistically have influence on intellectual capital disclosure, while corporate governance, leverage, profitability, listing age, and level of intellectual capital statistically do not have influence on intellectual capital disclosure of listed non-financial companies in Indonesia.